UV-photofunctionalization of a biomimetic coating for dental implants application - Dini, Caroline (2020)
Photofunctionalization mediated by ultraviolet (UV) rays changes the physico-chemical characteristics of titanium (Ti) and improves the biological activity of dental implants. However, the role of UV-mediated photofunctionalization of biofunctional Ti surfaces on the antimicrobial and photocatalytic activity remains unknown and was investigated in this study. Commercially pure titanium (cpTi) discs were divided into four groups: (1) machined samples without UV light application [cpTi UV−]; (2) plasma electrolytic oxidation (PEO) treated samples without UV light application [PEO UV−]; (3) machined samples with UV light application [cpTi UV+]; and (4) PEO-treated samples with UV light application [PEO UV+]. The surfaces were characterized according to their morphology, roughness, crystalline phase, chemical composition and wettability. The photocatalytic activity and proteins adsorption were measured. For the microbiological assay, Streptococcus sanguinis was grown on the disc surfaces for 1 h and 6 h, and the colony forming units and bacterial organization were evaluated. In addition, to confirm the non-cytotoxic effect of PEO UV +, human gingival fibroblast (HGF) cells were cultured in a monolayer onto each material surface and the cells viability and proliferation evaluated by a fluorescent cell staining method. PEO treatment increased the Ti surface roughness and wettability (p < 0.05). Photofunctionalization reduced the hydrocarbon concentration and enhanced human blood plasma proteins and albumin adsorption mainly for the PEO-treated surface (p < 0.05). PEO UV+ also maintained higher wettability values for a longer period and provided microbial reduction at 1 h of bacterial adhesion (p = 0.012 vs. PEO UV-). Photofunctionalization did not increase the photocatalytic activity of Ti (p > 0.05). Confocal microscopy analyses demonstrated that PEO UV+ had no cell damage effect on HGF cells growth even after 24 h of incubation. The photofunctionalization of a biofunctional PEO coating seems to be a promising alternative for dental implants as it increases blood plasma proteins adsorption, reduces initial bacterial adhesion and presents no cytotoxicity effect.